Balance of Payments Manual, Sixth Edition. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The sixth edition of the Balance of Payments and International Investment Position Manual presents revised and updated standards for concepts, definitions, and classifications for international accounts statistics. These standards are used globally to compile comprehensive and comparable data. The sixth edition is the latest in a series that the IMF began in 1948. It is the result of widespread consultation and provides elaboration and clarification requested by users. In addition, it focuses on developments such as globalization, financial market innovation, and increasing interest in balance sheet analysis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet